Desiccation Tolerance in Chlorophyllous Fern Spores: Are Ecophysiological Features Related to Environmental Conditions? - López-Pozo, Marina; Ballesteros, Daniel; Laza, José Manuel; García-Plazaola, José Ignacio; Fernández-Marín, Beatriz (Frontiers in Plant Science, 2019)
Fern spores of most species are desiccation tolerant (DT) and in some cases are photosynthetic at maturation, the so-called chlorophyllous spores (CS). The lifespan of CS in the dry state is very variable among species. Still, the physiological, biochemical and biophysical mechanisms underpinning this variability remains understudied and their interpretation from an ecophysiological point of view, virtually unexplored. In this work, we aimed at fulfilling this gap by assessing photochemical, hydric and biophysical properties of CS from three temperate species with contrasting biological strategies and longevity in the dry state: Equisetum telmateia (spore maturation and release in spring, ultra-short lifespan), Osmunda regalis (in summer, medium lifespan), Matteuccia struthiopteris (in winter, medium-large lifespan). After subjection of CS to controlled drying treatments, results showed that the three species displayed different degrees of DT. CS of E. telmateia rapidly lost viability after desiccation, while the other two withstood several dehydration-rehydration cycles without compromising its viabilities. These DT degrees were in concordance with water availability in the sporulation season of each species. Besides, CS of O. regalis and M. struthiopteris carried out the characteristic quenching of chlorophyll fluorescence, widely displayed by other DT cryptogams during drying, and higher tocopherol and proline contents. The turgor loss point of the CS also related to the extent of DT and to the sporulation season: lowest values were found in CS of M. struthiopteris and O. regalis. In addition, the hydrophobicity of spores in these two species was higher and probably related to the prevention of water absorption under unfavourable conditions. Molecular mobility, estimated by DMA, confirmed an unstable glassy state in the spores of E. telmateia, directly related to the low DT while the DT species entered in a stable glassy state when dried. Overall, our data revealed a DT syndrome related to the season of sporulation that was characterised by higher photoprotective potential, peculiar hydric properties and lower molecular mobility in the dry state. Being unicellular haploid structures CS represent a challenge for germplasm preservation (e.g. as these spores are prone to photooxidation) but also an exceptional opportunity for studying mechanisms of DT in photosynthetic cells.